2012
DOI: 10.1177/1359105311435945
|View full text |Cite
|
Sign up to set email alerts
|

Disordered eating behavior and body weight and shape relatives’ criticism in overweight and obese 15- to 19-year-old females

Abstract: This study evaluated the link between relatives' criticism of overweight or obese teenage girls' figure and body weight and their relationship with their mothers, fathers and siblings, affection, self-esteem, the internalization of the aesthetic body thin ideal, depressive symptoms and disordered eating behaviors (DEB). The sample comprised 2174 senior high school students aged 15 to 19. Teenagers criticized by their relatives showed higher DEB, without interaction between Body Mass Index (BMI) and DEB. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
1
21
0
8
Order By: Relevance
“…11,12 El IMC ha sido asociado anteriormente con la frecuencia de CAR en diferentes investigaciones en México. 8,[39][40][41] En este estudio, se encontró una prevalencia menor de sobrepeso y obesidad en los jóvenes participantes en comparación con los datos nacionales reportados en la ENSANUT-2012, 5 pero un porcentaje similar de CAR.…”
Section: Discusión Y Conclusiónunclassified
See 1 more Smart Citation
“…11,12 El IMC ha sido asociado anteriormente con la frecuencia de CAR en diferentes investigaciones en México. 8,[39][40][41] En este estudio, se encontró una prevalencia menor de sobrepeso y obesidad en los jóvenes participantes en comparación con los datos nacionales reportados en la ENSANUT-2012, 5 pero un porcentaje similar de CAR.…”
Section: Discusión Y Conclusiónunclassified
“…Tales hallazgos coinciden con lo reportado por Unikel et al, 39 quienes también reportaron un aumento en la frecuencia de CAR cuando aumenta el IMC en mujeres entre 15 y 19 años, así como la ausencia de interacción entre variables como crí-tica e IMC sobre la frecuencia de CAR. Este aumento en la frecuencia de CAR asociado con el aumento de IMC también fue reportado por Lora-Cortez y Saucedo-Molina 40 en una muestra de mujeres entre 25 y 45 años.…”
Section: Discusión Y Conclusiónunclassified
“…Still others have found greater perceived racism or everyday discrimination to be associated with greater weight gain across 8 years (Cozier et al, 2009), increases in waist circumference across 9 years (Hunte, 2011), and higher visceral fat (Lewis et al, 2011), or have found weight stigma to be associated with greater binge eating and less weight loss outcomes (Wott and Carels, 2010) as well as higher BMI and lower exercise motivation (Vartanian and Shaprow, 2008). Some recent work has found among adolescents that racial discrimination is associated with greater physical activity (Corral and Landrine, 2012), or that criticism by family members of adolescents considered overweight or obese is associated with greater disordered eating behaviors (Unikel Santoncini et al, 2013). Experiencing weight-based bullying has also been found to be associated with poorer eating and physical activity behaviors, as well as greater likelihood of being overweight over time, among adolescents (e.g.…”
Section: The Connections Of Discrimination and Bullying With Physicalmentioning
confidence: 99%
“…However, such ideals are almost impossible for most women to healthily achieve (Tiggemann, 2002), and women's experiences of pressure to attain this ideal is linked to body dissatisfaction, dieting behaviours and eating disorders (e.g. Halliwell & Dittmarr, 2004;Mask & Blanchard, 2011;Unikel Santoncini, Martin Martin, Juarez Garcia, Gonzalez-Forteza, & Nuno Gutierrez, 2012).…”
Section: Introductionmentioning
confidence: 99%